Fingolimod potentiates the antifungal activity of fluconazole against fluconazole-resistant Candida auris - Bae, Ji-Hui; Eom, Yong-Bin (Frontiers in Cellular and Infection Microbiology, 2025)
Candida auris has emerged as a critical nosocomial pathogen that particularly affects immunocompromised and critically ill patients in intensive care units, and it is associated with high mortality. The robust biofilm-forming ability and inherent fluconazole resistance of C. auris pose considerable treatment challenges. Consequently, novel therapeutic strategies are urgently needed to treat fluconazole-resistant C. auris (FRCA). This study investigated the antifungal effect of the combination of fluconazole with fingolimod against FRCA. The antifungal activity of fingolimod and resistance of C. auris to fluconazole were assessed using a minimum inhibitory concentration assay, and their interaction was evaluated through a checkerboard synergy assay. The combination treatment effectively inhibited early biofilm formation and eradicated mature biofilms, as demonstrated by the biofilm inhibition concentration and biofilm eradication concentration assays, respectively. The XTT reduction assay revealed a marked reduction in the metabolic activity of C. auris, which was further corroborated by confocal laser-scanning microscopy. Quantitative polymerase chain reaction revealed the downregulation of key virulence-associated genes, including ERG11 (azole resistance), CDR1 (efflux pump), and KRE6 (extracellular matrix). Collectively, these findings indicate that the combination of fingolimod and fluconazole inhibits biofilm formation, fungal metabolic activity, and virulence-related gene expression. This study suggests that fingolimod could serve as an adjuvant to improve the efficacy of fluconazole against FRCA.